Distribution and Physiology of ABC-Type Transporters Contributing to Multidrug Resistance in Bacteria - Lubelski, Jacek (American Society for Microbiology (ASM), 2007)
Summary: Membrane proteins responsible for the active efflux of structurally and functionally unrelated drugs were first characterized in higher eukaryotes. To date, a vast number of transporters contributing to multidrug resistance (MDR transporters) have been reported for a large variety of organisms. Predictions about the functions of genes in the growing number of sequenced genomes indicate that MDR transporters are ubiquitous in nature. The majority of described MDR transporters in bacteria use ion motive force, while only a few systems have been shown to rely on ATP hydrolysis. However, recent reports on MDR proteins from gram-positive organisms, as well as genome analysis, indicate that the role of ABC-type MDR transporters in bacterial drug resistance might be underestimated. Detailed structural and mechanistic analyses of these proteins can help to understand their molecular mode of action and may eventually lead to the development of new strategies to counteract their actions, thereby increasing the effectiveness of drug-based therapies. This review focuses on recent advances in the analysis of ABC-type MDR transporters in bacteria.